Pengaruh Senam Anak Indonesia Hebat Terhadap Peningkatan Kebugaran Jasmani Siswa Kelas V Di SDN Pasir Benteng II - Akbar Ramdani; Dinar Dinangsit; Encep Sudirjo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to evaluate the effectiveness of the Senam Anak Indonesia Hebat (SAIH) program in improving the physical fitness of fifth-grade students at SDN Pasirbenteng II. The research method used was a quantitative quasi-experimental design with a one-group pretest-posttest on 34 students selected through purposive sampling. Data were collected using the Indonesian Student Fitness Test (TKSI) package and analyzed using a paired t-test and the coefficient of determination (R2) test. Scientific findings showed a significant increase in all fitness variables (p < 0.05). The R2 test result of 0.796 proved that SAIH contributed 79.6% to improving student fitness. The conclusion of this study is that SAIH is a very effective and measurable physical exercise instrument to improve the physical quality of students in elementary schools. Keywords: Physical fitness, great indonesian children’s gymnastics.